Solar cell with high conversion rate and preparation method and application thereof

By forming a silicon carbide film on the silicon wafer of the solar cell, the problem that the PN junction after laser doping is easily eroded by the polishing liquid is solved, and the conversion efficiency of the solar cell and the performance of the silicon wafer are improved.

CN119584677APending Publication Date: 2025-03-07华能(嘉峪关)新能源有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411690412.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

During the preparation of solar cells, the PN junctions heavily doped after lasers are easily eroded by the polishing liquid, resulting in a decrease in the cell conversion efficiency.

Method used

A silicon carbide film is formed on the laser heavily doped silicon wafer. The silicon carbide film is formed by insulating heat at 600-900°C and passing carbon-containing organic matter and inert gas to form a silicon carbide film, so as to protect the PN junction from damage.

Benefits of technology

By forming a silicon carbide film, the PN junction is effectively protected, the conversion efficiency of solar cells is improved, and the high temperature, mechanical properties and corrosion resistance of the silicon wafer are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584677A_ABST
    Figure CN119584677A_ABST
Patent Text Reader

Abstract

The invention discloses a high-conversion-rate solar cell and a preparation method and application thereof. According to the invention, a layer of silicon carbide film is plated on the surface subjected to phosphorus doping after laser heavy doping, so that a PN junction is not damaged, meanwhile, a good passivation effect on a silicon wafer is achieved, and the conversion efficiency is improved. The silicon carbide layer is formed on the surface of the silicon wafer, so that the high-temperature resistance and the mechanical property of the surface of the silicon wafer are enhanced, and the service life of the silicon wafer is prolonged; the corrosion resistance of the surface of the silicon wafer is improved, and the stability of the silicon wafer in a severe environment is enhanced; the oxidation reaction on the surface of the silicon wafer is reduced, and the performance reduction caused by oxidation is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a high conversion rate solar cell and a preparation method and application thereof. Background Art

[0002] At present, solar cells are one of the mainstream high-efficiency cells on the market. Among them, SE-PERC cells are a laser heavy doping technology (SE) process added on the basis of PERC, which realizes the selective doping of solar cells, combines the front laser heavy doping technology (SE) with fine grid lines, improves the passivation effect, and significantly improves the open circuit voltage, thereby improving the conversion efficiency of solar cells. However, during the preparation process, the laser heavy doping technology needs to heavily dope the PN junction after phosphorus diffusion, and the oxide layer in the heavily doped area is easily damaged, so the heavily doped part of the PN junction will be exposed. In the subsequent polishing process of the back side, the polishing liquid will corrode the front PN junction, resulting in a decrease in the conversion efficiency of the cell. Therefore, it is urgent to develop a new process to protect the PN junction from being corroded by the polishing liquid. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0004] To this end, an embodiment of the present invention provides a high conversion efficiency solar cell and a preparation method and application thereof.

[0005] In a first aspect, the present invention provides a method for preparing a high conversion efficiency solar cell, comprising the following steps:

[0006] (a) Laser heavy doping of P-diffused silicon wafers;

[0007] (b) forming a layer of silicon carbide film on the surface to be heavily laser doped;

[0008] (c) removing the silicon-phosphorus glass on the back of the silicon wafer and performing etching and polishing;

[0009] (d) removing the silicon-phosphorus glass on the front side of the silicon wafer;

[0010] (e) after annealing, an aluminum oxide passivation film and a silicon nitride film are sequentially plated on the surface of the silicon wafer;

[0011] (f) Back-side laser grooving, screen printing, and sintering to obtain solar cells.

[0012] Furthermore, in step (a), the sheet resistance of the silicon wafer after P diffusion is 100-140Ω / sq, and the junction depth is 30-90nm; the sheet resistance of the silicon wafer after laser heavy doping is 55-75Ω / sq.

[0013] Further, the process of forming the silicon carbide film in step (b) comprises the following steps:

[0014] The heavily laser-doped silicon wafer is placed in a tube furnace, kept at 600-900°C for 5-15 minutes, and then vacuumed to 0.01-0.04 MPa;

[0015] Carbon-containing organic matter and inert gas are introduced into the gas to a pressure of 5 to 10 MPa, and the temperature is kept at 600 to 900° C. for 10 to 20 minutes to form a silicon carbide film on the P-doped side.

[0016] Furthermore, the method further comprises: releasing the pressure to normal pressure at a temperature of 600 to 900° C. and taking out the silicon wafer.

[0017] Furthermore, the carbon-containing organic matter includes one or more of methane, ethane, propane, ethylene, and propylene.

[0018] Furthermore, the flow rate of the carbon-containing organic matter is 3000-7000 sccm.

[0019] Furthermore, the thickness of the silicon carbide film is 20-130 nm.

[0020] Furthermore, the thickness of the aluminum oxide passivation film is 65-90 nm.

[0021] In a second aspect, the present invention proposes a solar cell prepared by the method proposed in the first aspect.

[0022] In a third aspect, the present invention proposes the use of a solar cell prepared by the method proposed in the first aspect or a solar cell proposed in the second aspect in an electrical device.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] The present invention plates a layer of silicon carbide film on the surface that is heavily laser doped and then phosphorus doped, so that the PN junction is not damaged and at the same time has a good passivation effect on the silicon wafer, thereby improving the conversion efficiency.

[0025] The present invention forms a silicon carbide layer on the surface of the silicon wafer, thereby enhancing the high temperature resistance and mechanical properties of the silicon wafer surface and extending the service life of the silicon wafer; improving the corrosion resistance of the silicon wafer surface and enhancing its stability in harsh environments; and reducing the oxidation reaction on the silicon wafer surface and avoiding the performance degradation caused by oxidation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0027] Figure 1 The present invention is a flow chart of the method for preparing a high conversion rate solar cell. DETAILED DESCRIPTION

[0028] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0029] Combined with Figure 1 The present invention is specifically described. The test materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources.

[0030] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0031] Example 1

[0032] S1: Select 500 P-type 2-4Ω.cm silicon wafers, first clean them with 6wt% hydrogen peroxide, then texturize them in 5wt% potassium benzoate and 8wt% sodium hydroxide, and finally clean and dry them to obtain the texturized silicon wafers. The weight of the silicon wafers after texturization is reduced by 0.3g, and the reflectivity of the silicon wafers is 10%.

[0033] S2: The silicon wafer after texturing is subjected to phosphorus diffusion and laser heavy doping treatment, wherein the square resistance of the silicon wafer after P diffusion is 120Ω / sq and the junction depth is 60nm; the square resistance of the silicon wafer after laser heavy doping is 65Ω / sq.

[0034] S3: Place the heavily laser-doped silicon wafer in a tubular furnace, keep it at 600°C for 15 minutes, and then evacuate to 0.01MPa; introduce carbon-containing organic methane gas with a flow rate of 3000sccm and inert gas nitrogen with a flow rate of 2000sccm to 5MPa, keep it at 600°C for 15 minutes, and form a silicon carbide film with a thickness of 30nm on the P-doped side; release the pressure to normal pressure at 600°C and take out the silicon wafer.

[0035] S4: Use 15wt% HF solution to remove the silicon phosphorus glass on the back of the silicon wafer, and use 0.6wt% sodium benzoate and 4wt% sodium hydroxide solution to etch and polish the back of the silicon wafer. After polishing, the weight of the silicon wafer is reduced by 0.25g, and the back reflectivity is 30%.

[0036] S5: Use 15wt% HF solution to remove the silicon-phosphorus glass on the front side of the silicon wafer; then anneal at 800°C, and the thickness of the silicon carbide film after annealing is 20nm; then aluminum oxide film and silicon nitride film are coated on the front and back sides of the silicon wafer in sequence, where the thickness of the aluminum oxide film is 65nm; the thickness of the silicon nitride film is 85nm.

[0037] S6: Laser groove the back of the silicon wafer, print the back electrode, back electric field and positive electrode; then sinter at 350°C to obtain a solar cell.

[0038] Example 2

[0039] S1: Select 500 P-type 2-4Ω.cm silicon wafers, first clean them with 6wt% hydrogen peroxide, then texturize them in 5wt% potassium benzoate and 8wt% sodium hydroxide, and finally clean and dry them to obtain the texturized silicon wafers. The weight of the silicon wafers after texturization is reduced by 0.3g, and the reflectivity of the silicon wafers is 10%.

[0040] S2: The silicon wafer after texturing is subjected to phosphorus diffusion and laser heavy doping treatment, wherein the square resistance of the silicon wafer after P diffusion is 120Ω / sq and the junction depth is 60nm; the square resistance of the silicon wafer after laser heavy doping is 65Ω / sq.

[0041] S3: Place the heavily laser-doped silicon wafer in a tubular furnace, keep it at 800°C for 10 minutes, and then evacuate to 0.02MPa; introduce carbon-containing organic ethane gas at a flow rate of 4000sccm and inert nitrogen gas at a flow rate of 2000sccm to 7MPa, keep it at 800°C for 10 minutes, and form a silicon carbide film with a thickness of 50nm on the P-doped side; release the pressure to normal pressure at 800°C and take out the silicon wafer.

[0042] S4: Use 14wt% HF solution to remove the silicon phosphorus glass on the back of the silicon wafer, and use 1wt% sodium benzoate and 4wt% sodium hydroxide solution to etch and polish the back of the silicon wafer. After polishing, the weight of the silicon wafer is reduced by 0.3g, and the back reflectivity is 35%.

[0043] S5: Use 15wt% HF solution to remove the silicon-phosphorus glass on the front side of the silicon wafer; then anneal at 600°C, and the thickness of the silicon carbide film after annealing is 45nm; then aluminum oxide film and silicon nitride film are coated on the front and back sides of the silicon wafer in sequence, where the thickness of the aluminum oxide film is 70nm; the thickness of the silicon nitride film is 80nm.

[0044] S6: Laser groove the back of the silicon wafer, print the back electrode, back electric field and positive electrode; then sinter at 350°C to obtain a solar cell.

[0045] Example 3

[0046] S1: Select 500 P-type 2-4Ω.cm silicon wafers, first clean them with 6wt% hydrogen peroxide, then texturize them in 5wt% potassium benzoate and 8wt% sodium hydroxide, and finally clean and dry them to obtain the texturized silicon wafers. The weight of the silicon wafers after texturization is reduced by 0.3g, and the reflectivity of the silicon wafers is 10%.

[0047] S2: The silicon wafer after texturing is subjected to phosphorus diffusion and laser heavy doping treatment, wherein the square resistance of the silicon wafer after P diffusion is 120Ω / sq and the junction depth is 60nm; the square resistance of the silicon wafer after laser heavy doping is 65Ω / sq.

[0048] S3: Place the heavily laser-doped silicon wafer in a tubular furnace, keep it at 900°C for 5 minutes, and then evacuate to 0.03MPa; introduce ethylene, a carbon-containing organic gas, at a flow rate of 5000sccm and nitrogen, an inert gas, at a flow rate of 2000sccm to 9MPa, and keep it at 900°C for 10 minutes to form a silicon carbide film with a thickness of 80nm on the P-doped side; release the pressure at 900°C to normal pressure and take out the silicon wafer.

[0049] S4: Use 15wt% HF solution to remove the silicon phosphorus glass on the back of the silicon wafer, and use 0.6wt% sodium benzoate and 3wt% sodium hydroxide solution to etch and polish the back of the silicon wafer. After polishing, the weight of the silicon wafer is reduced by 0.2g, and the back reflectivity is 40%.

[0050] S5: Use 15wt% HF solution to remove the silicon-phosphorus glass on the front side of the silicon wafer; then anneal at 700°C, and the thickness of the silicon carbide film after annealing is 60nm; then aluminum oxide film and silicon nitride film are coated on the front and back sides of the silicon wafer in sequence, where the thickness of the aluminum oxide film is 75nm; the thickness of the silicon nitride film is 85nm.

[0051] S6: Laser groove the back of the silicon wafer, print the back electrode, back electric field and positive electrode; then sinter at 350°C to obtain a solar cell.

[0052] Example 4

[0053] S1: Select 500 P-type 2-4Ω.cm silicon wafers, first clean them with 6wt% hydrogen peroxide, then texturize them in 5wt% potassium benzoate and 8wt% sodium hydroxide, and finally clean and dry them to obtain the texturized silicon wafers. The weight of the silicon wafers after texturization is reduced by 0.3g, and the reflectivity of the silicon wafers is 10%.

[0054] S2: The silicon wafer after texturing is subjected to phosphorus diffusion and laser heavy doping treatment, wherein the square resistance of the silicon wafer after P diffusion is 120Ω / sq and the junction depth is 60nm; the square resistance of the silicon wafer after laser heavy doping is 65Ω / sq.

[0055] S3: Place the heavily laser-doped silicon wafer in a tubular furnace, keep it at 700°C for 12 minutes, and then evacuate to 0.04MPa; introduce 7000sccm of carbon-containing organic gas propylene and 2000sccm of inert gas nitrogen to 10MPa, keep it at 700°C for 12 minutes, and form a silicon carbide film with a thickness of 120nm on the P-doped side; release the pressure to normal pressure at 700°C and take out the silicon wafer.

[0056] S4: Use 14wt% HF solution to remove the silicon phosphorus glass on the back of the silicon wafer, and use 1wt% sodium benzoate and 4wt% sodium hydroxide solution to etch and polish the back of the silicon wafer. After polishing, the weight of the silicon wafer is reduced by 0.5g, and the back reflectivity is 45%.

[0057] S5: Use 15wt% HF solution to remove the silicon-phosphorus glass on the front side of the silicon wafer; then anneal at 800°C, and the thickness of the silicon carbide film after annealing is 110nm; then aluminum oxide film and silicon nitride film are coated on the front and back sides of the silicon wafer in sequence, where the thickness of the aluminum oxide film is 85nm; the thickness of the silicon nitride film is 80nm.

[0058] S6: Laser groove the back of the silicon wafer, print the back electrode, back electric field and positive electrode; then sinter at 350°C to obtain a solar cell.

[0059] Comparative Example 1

[0060] S1: Select 500 P-type 2-4Ω.cm silicon wafers, first clean them with 6wt% hydrogen peroxide, then texturize them in 5wt% potassium benzoate and 8wt% sodium hydroxide, and finally clean and dry them to obtain the texturized silicon wafers. The weight of the silicon wafers after texturization is reduced by 0.3g, and the reflectivity of the silicon wafers is 10%.

[0061] S2: The silicon wafer after texturing is subjected to phosphorus diffusion and laser heavy doping treatment, wherein the square resistance of the silicon wafer after P diffusion is 120Ω / sq and the junction depth is 60nm; the square resistance of the silicon wafer after laser heavy doping is 65Ω / sq.

[0062] S3: Use 15wt% HF solution to remove the silicon phosphorus glass on the back of the silicon wafer, and use 0.6wt% sodium benzoate and 4wt% sodium hydroxide solution to etch and polish the back of the silicon wafer. After polishing, the weight of the silicon wafer is reduced by 0.25g, and the back reflectivity is 30%.

[0063] S4: Use 15wt% HF solution to remove the silicon-phosphorus glass on the front side of the silicon wafer; then anneal at 800°C; then coat aluminum oxide film and silicon nitride film on the front and back sides of the silicon wafer in sequence, wherein the thickness of the aluminum oxide film is 65nm; the thickness of the silicon nitride film is 85nm.

[0064] S5: Laser groove the back of the silicon wafer, print the back electrode, back electric field and positive electrode; then sinter at 350°C to obtain a solar cell.

[0065] Comparative Example 2

[0066] S1: Select 500 P-type 2-4Ω.cm silicon wafers, first clean them with 6wt% hydrogen peroxide, then texturize them in 5wt% potassium benzoate and 8wt% sodium hydroxide, and finally clean and dry them to obtain the texturized silicon wafers. The weight of the silicon wafers after texturization is reduced by 0.3g, and the reflectivity of the silicon wafers is 10%.

[0067] S2: The silicon wafer after texturing is subjected to phosphorus diffusion and laser heavy doping treatment, wherein the square resistance of the silicon wafer after P diffusion is 120Ω / sq and the junction depth is 60nm; the square resistance of the silicon wafer after laser heavy doping is 65Ω / sq.

[0068] S3: Use 14wt% HF solution to remove the silicon phosphorus glass on the back of the silicon wafer, and use 1wt% sodium benzoate and 4wt% sodium hydroxide solution to etch and polish the back of the silicon wafer. After polishing, the weight of the silicon wafer is reduced by 0.3g, and the back reflectivity is 35%.

[0069] S4: Use 15wt% HF solution to remove the silicon-phosphorus glass on the front side of the silicon wafer; then anneal at 600°C; then coat aluminum oxide film and silicon nitride film on the front and back sides of the silicon wafer in sequence, wherein the thickness of the aluminum oxide film is 70nm; the thickness of the silicon nitride film is 80nm.

[0070] S5: Laser groove the back of the silicon wafer, print the back electrode, back electric field and positive electrode; then sinter at 350°C to obtain a solar cell.

[0071] The electrical performance tests were conducted on Examples 1 to 4 and Comparative Examples 1 and 2. The test results are shown in Table 1.

[0072] Uoc(V) Isc(A) FF(%) NCell(%) Example 1 0.688 9.93 79.9 22.07 Example 2 0.686 9.89 80.4 22.13 Example 3 0.675 9.90 80.1 22.06 Example 4 0.671 9.89 80.5 21.86 Comparative Example 1 0.669 9.84 79.6 21.51 Comparative Example 2 0.664 9.85 79.5 21.52

[0073] It can be seen from Table 1 that compared with Comparative Examples 1 and 2, the conversion efficiency of the solar cells prepared in Examples 1 to 4 of the present invention is higher, reaching more than 21.86%; Comparative Examples 1 and 2 do not go through the step of forming a carbonized film, and therefore, the conversion efficiency is lower.

[0074] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0075] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0076] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a high conversion efficiency solar cell, characterized in that: The following steps are involved: (a) Laser heavy doping of P-diffused silicon wafers; (b) forming a layer of silicon carbide film on the surface to be heavily laser doped; (c) removing the silicon-phosphorus glass on the back of the silicon wafer and performing etching and polishing; (d) removing the silicon-phosphorus glass on the front side of the silicon wafer; (e) after annealing, an aluminum oxide passivation film and a silicon nitride film are sequentially plated on the surface of the silicon wafer; (f) Back-side laser grooving, screen printing, and sintering to obtain solar cells.

2. The method according to claim 1, characterized in that In step (a), the sheet resistance of the silicon wafer after P diffusion is 100-140Ω / sq, and the junction depth is 30-90nm; the sheet resistance of the silicon wafer after laser heavy doping is 55-75Ω / sq.

3. The method according to claim 1, characterized in that The process of forming the silicon carbide film in step (b) comprises the following steps: The heavily laser-doped silicon wafer is placed in a tube furnace, kept at 600-900°C for 5-15 minutes, and then vacuumed to 0.01-0.04 MPa; Carbon-containing organic matter and inert gas are introduced into the gas to a pressure of 5 to 10 MPa, and the temperature is kept at 600 to 900° C. for 10 to 20 minutes to form a silicon carbide film on the P-doped side.

4. The method according to claim 3, characterized in that Also includes: Release the pressure to normal pressure at 600-900°C and take out the silicon wafer.

5. The method according to claim 3, characterized in that The carbon-containing organic matter includes one or more of methane, ethane, propane, ethylene, and propylene.

6. The method according to claim 5, characterized in that The flow rate of the carbon-containing organic matter is 3000-7000 sccm.

7. The method according to claim 3, characterized in that The thickness of the silicon carbide film is 20-130 nm.

8. The method according to claim 1, characterized in that The thickness of the aluminum oxide passivation film is 65-90 nm.

9. A high conversion efficiency solar cell, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use the solar cell prepared by the method according to any one of claims 1 to 8 or the solar cell according to claim 9 in electrical equipment.